2011
DOI: 10.3399/bjgp11x578016
|View full text |Cite
|
Sign up to set email alerts
|

Open-access transvaginal sonography in women of reproductive age with abnormal vaginal bleeding: a descriptive study in general practice

Abstract: BackgroundDiagnostic ultrasonography is used by GPs in approximately 10% of patients of reproductive age with abnormal vaginal bleeding. Transvaginal sonography is recommended as a first-line diagnostic instrument for assessing uterine pathology. AimTo assess if findings resulting from openaccess sonography were in agreement with the GPs' working hypotheses and if these findings contributed to GPs' management. Design and settingProspective observational cohort study of GPs working in the health district of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Gastroscopy was the most commonly studied DA test (27 studies), followed by lower GI endoscopy (proctoscopy, flexible sigmoidoscopy, or colonoscopy, 15 studies), [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] CT (three studies -two head, one chest), [65][66][67] ultrasound (three studiestwo abdominal, one gynaecological), [68][69][70] MRI (three studies), [71][72][73] X-ray (two studies), 74,75 gastroscopy and lower endoscopy combined (two studies), 76,77 mammogram (one study), 78 mammogram and ultrasound combined (one study), 79 MRI and CT combined (one study), 80,81 transvaginal sonography (one study), 82 and a range of radiological tests including MRI, CT, and barium meal (one study). 83 Fifty-seven studies (95%) reported DA testing performed in a hospital or specialist clinic setting, one utilised a DA test located in primary care, 28 and two did not specify location.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastroscopy was the most commonly studied DA test (27 studies), followed by lower GI endoscopy (proctoscopy, flexible sigmoidoscopy, or colonoscopy, 15 studies), [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64] CT (three studies -two head, one chest), [65][66][67] ultrasound (three studiestwo abdominal, one gynaecological), [68][69][70] MRI (three studies), [71][72][73] X-ray (two studies), 74,75 gastroscopy and lower endoscopy combined (two studies), 76,77 mammogram (one study), 78 mammogram and ultrasound combined (one study), 79 MRI and CT combined (one study), 80,81 transvaginal sonography (one study), 82 and a range of radiological tests including MRI, CT, and barium meal (one study). 83 Fifty-seven studies (95%) reported DA testing performed in a hospital or specialist clinic setting, one utilised a DA test located in primary care, 28 and two did not specify location.…”
Section: Resultsmentioning
confidence: 99%
“…Across the remaining 14 studies reporting data to allow the calculation of cancer and other diagnoses CR, the cancer CR ranged from 0.0% for transvaginal sonography for abnormal vaginal bleeding to 11.7% in a study reporting a wide range of DA tests used at the GPs' discretion. 82,83 The conversion rate for non-cancer diagnosis ranged from 4.2% for patients undergoing mammogram to 56.4% in a study reporting the use of DA X-ray used at GPs' discretion. 75,78 (Further information is available from the authors on request.)…”
Section: Other Testsmentioning
confidence: 99%
“…Abnormal uterine bleeding is a common problem that accounts for up to 30% of outpatient visits to gynecologists [1][2][3]. In premenopausal women, it is the single most common reason for gynecological referrals.…”
Section: Introductionmentioning
confidence: 99%